2015
DOI: 10.1530/jme-14-0274
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin, a novel adipokine, stimulates glucose uptake through the Ca2+-dependent AMPK–p38 MAPK pathway in C2C12 skeletal muscle cells

Abstract: Visfatin is a novel adipocytokine produced by visceral fat. In the present study, visfatin increased AMP-activated protein kinase (AMPK) phosphorylation in mouse C2C12 skeletal muscle cells. It also increased phosphorylation of the insulin receptor, whose knockdown blocked visfatin-induced AMPK phosphorylation and glucose uptake. Visfatin stimulated glucose uptake in differentiated skeletal muscle cells. However, inhibition of AMPKa2 with an inhibitor or with knockdown of AMPKa2 using siRNA blocked visfatin-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…In the present study, we proposed a mechanism by which MR blockade improves adiponectin expression. The activation of the AMPK/p38 MAPK signaling cascade stimulates glucose uptake in adult cardiomyocytes, and the inhibition of the p38 MAPK signaling pathway abolishes the stimulation of glucose uptake in response to hypoxia [28,29]. In muscle cells, adiponectin activates AMPK and p38MAPK, which sequentially stimulates PPARα activity [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we proposed a mechanism by which MR blockade improves adiponectin expression. The activation of the AMPK/p38 MAPK signaling cascade stimulates glucose uptake in adult cardiomyocytes, and the inhibition of the p38 MAPK signaling pathway abolishes the stimulation of glucose uptake in response to hypoxia [28,29]. In muscle cells, adiponectin activates AMPK and p38MAPK, which sequentially stimulates PPARα activity [30].…”
Section: Discussionmentioning
confidence: 99%
“…pathways. Recent studies also indicated that visfatin and isoeugenol causes increased uptake of glucose in adipocytes and myocytes (Kim et al, 2016), in which AMPKa2 subunit promotes GLUT4 gene expression (Lee et al, 2015), consistent with earlier studies showing that AICAR/ AMPK enhanced glucose intake in muscle (Sakoda et al, 2002). In addition, overexpression of HDAC5 represses GLUT4 gene expression, and AICAR/AMPKa2 phosphorylates HDAC5 at S259 and S498 reduces nuclear HDAC5 resulting in decrease of HDAC5 binding with the GLUT4 promoter thereby promoting GLUT4 gene expression (Li et al, 2008) (Figure 2).…”
Section: Ampk and Glucose/fatty Acid Transportmentioning
confidence: 99%
“…Most recently, experimental and clinical studies suggest that novel adipokines such as adipsin and visfatin might have an energetic role in the cascade of the events leading to diabetes mellitus. Namely, adipsin has a beneficial role in maintaining β cell function and visfatin plays an important role in glucose metabolism (2,3).…”
Section: Introductionmentioning
confidence: 99%